Mapping Non-Performing Assets: Figures from Dimension AI database - Thapa, Labita (NPRC Journal of Multidisciplinary Research, 2024)
The issue of non-performing assets (NPAs) or non-performing loans (NPLs) presents a significant challenge in the financial sector, affecting the stability and profitability of financial institutions globally. Conducting a bibliometric analysis of NPLs aims to understand the current research landscape and identify opportunities for future study, ultimately contributing to the development of effective strategies to manage and mitigate the impact of NPLs. Systematic review analyzes articles in Banking, Finance, and Investment, focusing on Non-Performing Assets (NPAs) or Non-Performing Loans (NPLs) published between 2020 and 2024. 33 documents were selected based on relevance to the topic. Through rigorous filtering and review, key insights, methodologies, and findings were extracted from the selected articles. Articles related to Non-Performing Assets/Loans, the Malaysian Management Journal emerged as the most cited publication, with five citations. The research conducted by the Institute of Cost Accountants of India and Vidyasagar University also garnered considerable attention. Among the individual papers, those authored by Maity and Tarak Nath received five citations each. The findings of the study highlighted key themes including Efficiency Decline, NPL Impact on Performance, Capital Adequacy Influence, Credit Risk Moderation, Persistent NPA Challenges, and Complex Factors Contributing to NPLs. These findings underscore the multifaceted nature of NPAs and NPLs, emphasizing their significant impact on the banking and finance sector. Study underlines landscape of NPAs/NPLs, identifying key themes, influential publications, and authors, thus guiding future research directions and strategic interventions for managing NPAs/NPLs in the financial sector. bibliometric analysis of NPAs/NPLs in Banking, Finance, and Investment fields from 2020 to 2024.